2022
DOI: 10.3389/fcvm.2022.906021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of central blood pressure measured by radial tonometry and automated office blood pressure measured using automatic devices in cardiovascular diseases

Abstract: ObjectiveCentral aortic systolic blood pressure (CBP) measured by carotid-femoral pulse wave analysis (cfPWA) is a gold standard method to estimate true arterial pressure. However, the impact of the CBP level measured by radial PWA on cardiovascular (CV) risk assessment is unclear. This study aimed to determine the impact on CV outcome assessment and the association between the optimal levels of non-invasively measured CBP and automated office blood pressure (OBP) in clinical practice.Materials and methodsA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In Figure 2, using a categorical approach, CBP at 120mmHg and SBP at 140mmHg might be divided into normotensive and hypertensive levels based on our previous study and Korea guideline [3,[13][14][15]. Group 1 (isolated central hypertension group, consisting of high CBP and normal SBP) had a total of 162 patients, with average values for age, BMI, CBP, SBP, DBP, PP, and CPP of 57.2 ± 10.8 years, 24.2 ± 3.1 kg/m 2 , 126.4 ± 4.5 mmHg, 132.1 ± 4.8 mmHg, 81.0 ± 7.9 mmHg, 51.0 ± 8.0 mmHg, and 45.5 ± 8.6 mmHg, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 2, using a categorical approach, CBP at 120mmHg and SBP at 140mmHg might be divided into normotensive and hypertensive levels based on our previous study and Korea guideline [3,[13][14][15]. Group 1 (isolated central hypertension group, consisting of high CBP and normal SBP) had a total of 162 patients, with average values for age, BMI, CBP, SBP, DBP, PP, and CPP of 57.2 ± 10.8 years, 24.2 ± 3.1 kg/m 2 , 126.4 ± 4.5 mmHg, 132.1 ± 4.8 mmHg, 81.0 ± 7.9 mmHg, 51.0 ± 8.0 mmHg, and 45.5 ± 8.6 mmHg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is thought that CBP may be more advantageous than brachial BP, which is mainly measured at the office, in evaluating target organ damage in normotensive patients [17, 18]. Therefore, our previous study showed that CV risk increased rapidly at a CBP of 120 mmHg or higher through previously studied CBP data, irrespective of the brachial BP status [13-15]. In a recent meta-analysis, optimal CBP and central hypertension were defined as less than 110 mmHg and 120 mmHg, respectively, based on the primary CV endpoint with a 5-year probability of cohort data [10].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of the observed reductions in central SBP in healthy young men is currently unknown and warrants additional investigation. However, central SBP readings > 125 mmHg are associated with a significant increase in atherosclerotic cardiovascular outcomes, and for every 10 mmHg increase in central SBP the risk of an adverse cardiovascular outcomes increases by 11.7% (Kwon et al 2022 ). This is important since resolving the time of day that administration of antihypertensive interventions elicits the optimal effects on cardiovascular health and cardioprotection remains unclear and an active area or research in cardiovascular medicine (Mackenzie et al 2022 ; Hermida et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%